2013
DOI: 10.1017/s1751731112002066
|View full text |Cite
|
Sign up to set email alerts
|

Soybean isoflavone reduces the residue of zearalenone in the muscle and liver of prepubertal gilts

Abstract: The aim of the present study was to evaluate the protective effects of isoflavone (ISO) against zearalenone (ZEA) residues in the muscle and liver tissues of prepubertal gilts. Seventy 75-day-old, prepubertal, female pigs (Duroc 3 Landrace 3 Yorkshire, 26.5 6 0.60 kg) were allocated randomly to seven diet treatments for 21days as follows: one control group (fed the basal diet) and six groups fed the basal diet with the addition of either 0.5 or 2.0 mg/kg ZEA plus either 0, 300 or 600 mg/kg ISO. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…ZEA and its metabolites are agonists of ERα (they are observed mainly in the uteri, but not in the ovaries) [ 43 ]. The addition of 0.5 to 2 mg/kg ZEA in the diet has been shown to significantly increase the transcription level of ERα in the uteri and vaginal tissue of gilts, whereas it significantly reduced the transcription level of ERβ, which regulates the development of reproductive organs [ 44 ]. The mechanism whereby ZEA acts on sow uteri can probably be explained by the fact that α-ZOL has a high affinity for endometrial estrogen receptors, and competes with estrogen for target tissue receptors to promote the synthesis of DNA, RNA, and protein.…”
Section: Discussionmentioning
confidence: 99%
“…ZEA and its metabolites are agonists of ERα (they are observed mainly in the uteri, but not in the ovaries) [ 43 ]. The addition of 0.5 to 2 mg/kg ZEA in the diet has been shown to significantly increase the transcription level of ERα in the uteri and vaginal tissue of gilts, whereas it significantly reduced the transcription level of ERβ, which regulates the development of reproductive organs [ 44 ]. The mechanism whereby ZEA acts on sow uteri can probably be explained by the fact that α-ZOL has a high affinity for endometrial estrogen receptors, and competes with estrogen for target tissue receptors to promote the synthesis of DNA, RNA, and protein.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [102] studied the effects of dietary soybean isoflavone on zearalenone residues in the muscle and liver of young female pigs and demonstrated that addition of zearalenone into the diet increased protein expression of 3α/3β-HSD. Interestingly, the addition of isoflavones to the zearalenone-contaminated diet decreased the hepatic protein expression of 3α/3β-HSD compared with the addition of zearalenone alone.…”
Section: Dietary Influence On 3β-hsdmentioning
confidence: 99%
“…Soybean residue contains protein, carbohydrates, dietary fiber, isoflavone, and minerals (Li et al, ; O'Toole, ). It has antioxidant activity and may aid in prevention of diabetes, obesity, and hyperlipidemia (Li et al, ; Li et al, ; Li et al, ; Wang, Zhou, Hou, Qi, & Zhang, ). However, soybean residue is not widely used in food because of its high moisture content and poor edible quality.…”
Section: Introductionmentioning
confidence: 99%